Observing the Objective Structured Clinical Exam: A Deeper Dive into Structured Clinical Examination - Azhar, Tayyaba; Nasreen, Maimoona; Malik, Khizar Ansar; Aslam, Kinza; Mukhtar, Sara; Rafique, Saima (Pakistan Armed Forces Medical Journal, 2023)
Objective: To explore the perceptions of students and examiners regarding objective structured clinical examination (OSCE). Study Design: Cross-sectional study. Place and Duration of Study: University College of Medicine & Dentistry, Lahore Pakistan from Dec to Apr 2023. Methodology: Data was collected through Google Forms, which served as a secure and user-friendly platform for survey administration. Data was collected from the students who were enrolled in the integrated curriculum. The research involved administering a pre-validated questionnaire to 40 examiners and 272 fourth- and final-year MBBS students. The questionnaire aimed to gather insights into various aspects of the objective structured clinical examination (OSCE), including its attributes, structure, and validity. Results: The mean attributes of OSCE were analysed, the students’ perceptions of organization, validity, and reliability were 3.52±0.72, 3.6±0.79, and 3.69±0.75, respectively. Examiners addressed clinical knowledge, skills, and station organisation SCE’s positive impact. 47.5% of faculty faced equipment challenges, while 30% of examiners did not find OSCE stressful. Conclusion: The study examines organisational and examiner views on OSCE, highlighting its effectiveness in teaching clinical skills and knowledge.